2014
DOI: 10.1590/s0102-77862014000200013
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da temperatura basal inferior para as cultivares de oliveira Grappolo e Maria da Fé

Abstract: A temperatura basal inferior (Tb) é uma variável de entrada muito utilizada em modelos que quantificam o desenvolvimento de culturas agrícolas e florestais. O objetivo deste trabalho foi estimar a Tb para o desenvolvimento vegetativo na fase de muda, para duas cultivares de oliveira, Grappolo e Maria da Fé, em condições de campo. O estudo foi desenvolvido na área Experimental da Empresa de Pesquisa Agropecuária de Minas Gerais, em Maria da Fé, MG, Brasil, conduzido sob o delineamento inteiramente casualizado, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
2
8
0
3
Order By: Relevance
“…Even though nonlinear development models, such as WE, are preferred because they describe the development of plants (Erpen et al, 2013) in a more realistic way and are applied under conditions of great temperature variation (Martins et al, 2014), the FIL model showed superior performance in the simulation of LN for guava. Similar results were obtained by Martins et al (2014) in the LN simulation and duration of the seedling phase for 'MGS ASC315' olive cultivar, by Monteiro et al (2014) in seedlings of Adenanthera pavonina L., Cassia fistula L., Hymenolobium petraeum Ducke and Parkia pendula Willd., by Erpen et al (2013) in the vegetative development of sweet potato, and Streck et al (2007) in the vegetative and reproductive development of rice genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though nonlinear development models, such as WE, are preferred because they describe the development of plants (Erpen et al, 2013) in a more realistic way and are applied under conditions of great temperature variation (Martins et al, 2014), the FIL model showed superior performance in the simulation of LN for guava. Similar results were obtained by Martins et al (2014) in the LN simulation and duration of the seedling phase for 'MGS ASC315' olive cultivar, by Monteiro et al (2014) in seedlings of Adenanthera pavonina L., Cassia fistula L., Hymenolobium petraeum Ducke and Parkia pendula Willd., by Erpen et al (2013) in the vegetative development of sweet potato, and Streck et al (2007) in the vegetative and reproductive development of rice genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The following two models were used to simulate the development: phyllochron (FIL) and Wang and Engel (WE); and the simulation was performed in two stages (Martins et al, 2014). The first stage was related to the adjustment of the coefficients to the models FIL and LARmax (data from E1 to E5), and the second evaluated the performance (data from E6 to E12).…”
Section: Methodsmentioning
confidence: 99%
“…Ferreira et al (2019) estimated the cardinal development temperatures for guava seedlings, applying 12 different models with methodologies based on the standard deviation of the accumulated degree days of growth, calculating the base (minimum) temperature as 10.9ºC, the optimum as 17.3ºC and the maximum as 51.2ºC. There is little information on cardinal temperatures in fruit species, which are very useful for studies on adaptation to different microclimates (Souza and Martins, 2014).…”
Section: Temperaturementioning
confidence: 99%
“…The cardinal temperatures are normally determined under field conditions, at different sowing/planting times, to ensure that the plants are subjected to different thermal conditions (SOUZA & MARTINS, 2014). However, the lower base and upper base temperatures rarely occur under field conditions in southern Brazil, which predominantly experiences subtropical climate, necessitating further study in temperature-controlled environments.…”
Section: Introductionmentioning
confidence: 99%